Business and human rights: Understanding the UN Guiding Principles from the perspective of transnational business governance interactions. (3rd April 2015) - Buhmann, Karin
Abstract : This article analyses the United Nations (UN) Guidelines on Business and Human Rights adopted in 2011 by the UN Human Rights Council from the perspective of transnational business governance interactions (TBGI) analytical framework. 1 The article identifies and discusses dimensions of interaction and components of regulatory governance which characterize the Guiding Principles, focusing in particular on rule formation and implementation. The article notes that the Guiding Principles actively enrolled other actors for the rule-making process, ensuring support in a politically and legally volatile field. It identifies mutual 'piggy-backing' by the Guiding Principles and other TBGI schemes, complementing the Principles' very limited limitation and enforcement modalities and lending support to rule-making and implementation of other schemes. The article concludes that the UN Guiding Principles are unique in several areas of relevance to transnational business governance interaction and indicates the relevance of the TBGI approach to public regulatory transnational business governance initiatives. The analysis of the Guiding Principles as interactional transnational business governance suggests that this form of governance offers prospects for public institutions as a means towards regulating global sustainability concerns.